2004
DOI: 10.1063/1.1828215
|View full text |Cite
|
Sign up to set email alerts
|

Shock wave compression of the ferroelectric ceramic Pb0.99(Zr0.95Ti0.05)0.98Nb0.02O3: Depoling currents

Abstract: Shock wave compression of poled Pb0.99(Zr0.95Ti0.05)0.98Nb0.02O3 (PZT 95/5-2Nb) results in rapid depoling and release of bound charge. In the current study, planar-impact experiments with this material were conducted on a gas-gun facility to determine Hugoniot states, to examine constitutive mechanical properties during shock propagation, and to investigate shock-induced depoling characteristics. A previous article summarized results from the first two of these areas, and this article summarizes the depoling s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
34
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(42 citation statements)
references
References 21 publications
5
34
0
Order By: Relevance
“…These PZT 52/48 and 95/5 results are in good agreement with previous results of transverse depolarization of the two ferroelectrics1721.…”
Section: Methodssupporting
confidence: 92%
“…These PZT 52/48 and 95/5 results are in good agreement with previous results of transverse depolarization of the two ferroelectrics1721.…”
Section: Methodssupporting
confidence: 92%
“…First, the initial currents for PZT95/5 ceramic and PIN‐PMN‐PT crystals are opposite in direction. At 3.0 GPa pressure, the polarization vector of PZT95/5 ceramic changes from initial value to zero with the occurrence of FE‐AFE phase transitionThe current direction of PIN‐PMN‐PT crystals keeps opposite to that of PZT95/5, it is confirmed that the polarization of PIN‐PMN‐PT is increased under shock wave compression. Second, different from PZT95/5, PIN‐PMN‐PT crystal has reversed current after negative current.…”
Section: Resultsmentioning
confidence: 67%
“…Since Neilson reported the rapid depolarization of ferroelectric ceramics induced by shock waves compression in 1957, numerous investigations on the ferroelectric materials under shock wave compression have been reported. Due to the application of explosively driven pulsed power supply, the research in this field mainly focused on the ferroelectric–antiferroelectric (FE‐AFE) phase transition induced by shock compression . The ferroelectric ceramics with composition close to the FE/AFE phase boundary, such as (PbZr 0.95 Ti 0.05 O 3 ) PZT95/5, present a small free energy difference between FE and AFE phases, and the FE‐AFE phase transition could be easily induced by pressure.…”
Section: Introductionmentioning
confidence: 99%
“…The same phenomenon was also observed in porous PZT 95/ 5 at 2.4 GPa, which was due to dynamic yielding, but porous PZT 95/5 behaves normally at 3.0 GPa. 10 Thus, mechanical failure at low stresses did not immediately cause electrical breakdown, even when cracks were already present in the PZT 95/5. This only occurred when the stress was increased to 4.3 GPa and the samples were full of the cracks, in which case 100% electrical breakdown was observed and the breakdown strength decreased.…”
Section: Dielectric Properties Under Different Stressesmentioning
confidence: 93%
“…For PZT 95/5, the empirical equation for P fsc is 10 ðP r À P f sc Þ=P r ¼ 1:26 À 0:59r À1 s ; 0:5 < r s < 2:5; (2) where r s is the shock stress in GPa. According to Kirchhoff's current and voltage laws, the relationships below were obtained…”
Section: B Analysis Of the Equivalent Circuitmentioning
confidence: 99%